Students problem-solving skills ability on work and energy topics with different science process skills using a problem-based learning model - Denda Nadia Miranti; Ahmad Harjono; Satutik Rahayu (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2022)
This study aims to: (1) determine the effect of the problem-based learning model on students' problem-solving abilities; (2) study the effect of science process skills on students' problem-solving abilities; (3) find the interaction between problem-based learning PBL models and science process skills on students' problem-solving abilities. The type of research is quasi-experimental research with Factorial Design 2 x 2. Population in research of all tenth-grade science students at senior high school SMA Negeri 1 Gunungsari in 2017/2018 academic years. Sampling in this study uses the cluster random sampling technique, in which the X MIA is an experiment class, and the X MIA 1 is a control class. The research instrument used was a description test taking into account the problem's validity, reliability, power difference, and level of difficulty and using observation sheets of science process skills. The data of this study were analyzed by two-way variance analysis with a 2 x 2 factorial design. Based on the result of the study, the average value of the post-test experimental class was 80.29, and the control class was 73.25. The normality and homogeneity tests showed that the two classes were normally distributed and homogeneous at a significant level of 0.05. Then proceed with hypothesis testing using a two-way ANOVA test. The result showed that: (1) FA>Ftable that is 29.35>4.02 means that there is an influence of the PBL model on students' problem-solving abilities; (2) FB>Ftable, namely 29.35 > 4.02 means that there is an influence of science process skills on students' problem-solving abilities; (3) FAB< Ftable, is 3.93<4.02 means that there is no interaction between PBL models and science process skills on students' problem-solving abilities.